Analysis Calculation Of Cost Of Goods Production And Selling Prices Full Costing Method In Sharia Accounting Perspective - Wifka Yunita; Kamilah K; Marliyah, Marliyah (SEAN Institute, 2024)
The role of calculating selling prices and production costs is crucial for being able to compete with products from industries and SMEs out there. This study aims to analyze all costs incurred during the opaque production process to determine the production costs and selling prices at Eka Jaya Opak. Researchers used qualitative research with a descriptive approach. Qualitative descriptive methods were used in determining product prices and selling prices. The problem at hand is how to determine production costs and selling prices using the full costing method and comparing the results with the factory method. Based on the results of this research, the production cost using the factory method is Rp. 6,681, while the full costing method is Rp. 7,048. There is a clear difference between the factory method costs and the full costing method costs, which is Rp. 367. And the selling price of the production is Rp. 8,018, while the full costing method is Rp. 8,458 with a difference of Rp. 440.